Air inclusions in the polymer melt functioning as intrinsic physical blowing agents for the generation of foams in rotational molding - Werner, Jannik; Vetter, Lukas; Hertle, Sebastian; Wolf, Michael; Drummer, Dietmar (Cellular Polymers, 2020)

Influence of Vacuum on the Porosity and Mechanical Properties in Rotational Molding - Vetter, Lukas; Werner, Jannik; Wolf, Michael; Hertle, Sebastian; Drummer, Dietmar (Polymer Engineering and Science, 2019)
Rotational molding allows the production of seamless, hollow parts with a high degree of design flexibility. Nevertheless, the process has limitations such as long cycle times as long holding times are necessary to produce components free of air inclusions. Within the scope of this article, an experimental setup was developed to evaluate the possibility and resulting effects of using vacuum in the rotational molding process. For this purpose, trials with different vacuum pressure levels and holding times were carried out and the resulting porosity and surface quality as well as the mechanical properties of the specimens were determined. The investigations showed that the use of vacuum allows a significant reduction in porosity even at low holding times, which can considerably reduce the cycle time of the process. However, the extent of possible time saving is limited by the requirement of a good surface quality, on which the vacuum application shows no effect. Furthermore, the mechanical properties of the parts could be slightly improved by using vacuum. POLYM. ENG. SCI., 2019. © 2019 Society of Plastics Engineers.
CRIS-Team Scopus Importer:2019-06-25